Coumarinylmethyl Caging Groups with Redshifted Absorption. Issue 51 (11th November 2013) - Fournier, Ludovic; Aujard, Isabelle; Le Saux, Thomas; Maurin, Sylvie; Beaupierre, Sandra; Baudin, Jean‐Bernard; Jullien, Ludovic
Abstract The small and synthetically easily accessible coumarinylmethyl backbone has been modified to generate a family of photolabile protecting groups with redshifted absorption. We relied on introducing electron‐donating groups in the 7 position and electron‐withdrawing groups in the 2‐, and 2‐ and 3 positions. In particular, we showed that the diethylamino‐thiocoumarylmethyl and the diethylamino‐coumarylidenemalononitrilemethyl are relevant for uncaging with cyan light. They both exhibit a significant action cross section for uncaging in the 470–500 nm wavelength range and a low light absorption between 350 and 400 nm. These attractive features are favorable to perform chromatic orthogonal photoactivation with UV and blue‐cyan light sources, respectively.